Time-dependent power law function for the post-dealloying chemical coarsening of nanoporous gold derived using small-angle X-ray scattering. (1st January 2022) - Ng, Alexander K.; Welborn, Samuel S.; Detsi, Eric
Abstract: Dealloyed nanoporous gold spontaneously coarsens when exposed to moderate temperatures (thermal coarsening), or to non-inert gases or liquids at room temperature (chemical coarsening). Although considerable research has been done on post-dealloying thermal coarsening, little attention has been paid to post-dealloying chemical coarsening, occurring not during, but after dealloying. Here, we use small- and wide-angle X-ray scattering (SAXS/WAXS) techniques to study the post-dealloying chemical coarsening behavior of dealloyed nanoporous gold samples aged in nitric acid over the course of 6 days at room temperature. A quantitative relationship between the ligament size and coarsening time is derived. Typically, our SAXS data reveals that the ligament size in nanoporous gold chemically coarsens according to a ∼1/4 time-dependent power law, which is characteristic of a surface diffusion-dominated process. The derived relationship between the ligament size and coarsening time will guide the design of nanoporous gold with desired structure size to optimize its (electro)chemical properties. Graphical abstract: Image, graphical abstract